A theoretical study of hydrogen adsorption on Ru-decorated (8,0) single-walled carbon nanotube - Verdinelli, Valeria (2014)
adsorption on Ru-decorated (8,0) zigzag single-walled carbon nanotube (SWCNT) was studied using density functional theory (DFT). Several decoration sites on the CNT surface were investigated before atomic or molecular hydrogen adsorption. The most stable location for a single Ru atom is above the hollow site, with an adsorption energy of Eads(Ru) = −2.133 eV. Ru decoration increases hydrogen adsorption energy nearly 46% compared to pristine CNT. When a hydrogen molecule is considered on Ru/SWCNT its adsorption is dissociative with an Eads(H2) = −0.697 eV. The Ru-decorated SWCNT systems exhibit magnetic properties. Density of states (DOS) and overlap population density of states (OPDOS) were computed in order to study the evolution of the chemical bonding. C–C bonds interact with Ru and are weakened after adsorption. Strong Ru–H bonds are formed during hydrogen adsorption process at expenses of C–Ru bonds. The mains interactions include the Ru 5pz and 4dz2 and C 2pz bands.